Revitalization of Islamic Religious Education in Answering the Challenges of the Digital Era - Muhammad Adip Fanani; M Iqbal Abdurrohman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The digital revolution has brought great challenges as well as opportunities in education, including Islamic religious education (PAI). This article discusses the revitalization of PAI to answer the needs of the digital era with two main focuses: the current condition of Islamic religious education and strategic steps to carry out revitalization. The research method used is library research with data analysis from various literature sources related to the revitalization of PAI in the modern era. The results of the study indicate that curriculum digitalization, improving teacher competence, developing digital learning resources, and integrating Islamic values ​​with technology are strategic steps that need to be implemented. Collaborative support between the government, educational institutions, and the community is needed to create relevant, inclusive, and competitive Islamic religious education.